Parlour Games and the Public Life of Women in Renaissance Italy - McClure, George W., 1951- (Book collections on Project MUSE., 2013)
Confined by behavioural norms and professional restrictions, women in Renaissance Italy found a welcome escape in an alternative world of play. This book examines the role of games of wit in the social and cultural experience of patrician women from the early sixteenth to the early eighteenth century.